Pengaruh Kemampuan Awal terhadap Hasil Belajar Matematika - Prana Hevriansyah; Priarti Megawanti (Universitas Indraprasta PGRI, 2016)
This research is aimed to acknowledging the impacts of previous ablity on the result of learning mathematics . Previous ability in this research is students’ basic ability of mathematics. The research is corrasional survey with simple regression analysis on the students X grade at SMK Negeri 2 Cikarang Barat. Sample in the research is 50 respondents taken from the number of population reach as many as 481 respondents. The instrument used is written test in the form of multiple choice and essay. the data was analyzed descriptively and inferensial after the data fulfill normality test and linnearity test and the result show that tcount > ttable (4.426 > 2.001). So it can be concluded that in 50 % significancy, there are significant impacts of previous ability on the result of learning mathematics.